Model for the improvement of organizational performance through the practices of quality management, knowledge management and transformational leadership in a private university - Coaquira Tuco, Carlos Mediver (2018)
The purpose of this research study was to validate the causal relationships according to the proposed theoretical model, explaining that the improvement of organizational performance is developedthrough quality management practices, knowledge management and transformational leadership. To achieve this, a questionnaire was applied to a convenience sample of 222 administrators and teachers of a private university. The research design was consideredas multiple correlational with a transversal focus. The data was analyzed by means of a system of structural equations. The parameters obtained to assess the goodness of fit of the model were the following: x2with a value of 2463.580, x2/ gl of 1.582 less than or equal to 3.0, RMSEA of 0.051 less than or equal to .07, GFI of 0.736 greater than or equal to .70, and CFI of .903 greater than or equal to .90, these indices reveal a very good adaptation of the structure and validation of the proposed model, as well as that all causal relations in the model (p-value <0.05) are statistically significant. Thus it is affirmed that the development of the organizational performance is affected by the interactions of the practices of quality management, knowledge management and transformational leadership.